Characterizations of a helicoid and a catenoid - Yuzbasi, Zuhal Kucukarslan; Yoon, Dae Won (Hacettepe Univ, Fac Sci, 2022)
In the present article, we consider a parametric surface generated by the Frenet frame of a curve, and study the minimality condition for the surface. As a result, we give characterizations of a helicoid and a catenoid. Finally we show some examples of minimal surfaces generated by a circle and a helix.
Keywords: minimal surface; catenoid; helicoid; marching-scale function